2022
DOI: 10.1128/spectrum.00133-22
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Viability Depends on the Ecological Setting of Hosts within a Multiplasmid Community

Abstract: Conjugative and mobilizable plasmids are ubiquitous in bacterial systems. Several different plasmids can compete within a single bacterial community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…There was a significant distinction in the higher rescue potential of the RP4 plasmid compared to the other pEC plasmids. Certain pEC plasmids, pEC15 and pEC14, had little to no rescue potential, which is consistent with the previous studies using these plasmids ( 36 , 56 ). Little correlation could be drawn between the rescue potential and certain plasmid characteristics such as Inc type, mobility class, and mating pair formation systems.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was a significant distinction in the higher rescue potential of the RP4 plasmid compared to the other pEC plasmids. Certain pEC plasmids, pEC15 and pEC14, had little to no rescue potential, which is consistent with the previous studies using these plasmids ( 36 , 56 ). Little correlation could be drawn between the rescue potential and certain plasmid characteristics such as Inc type, mobility class, and mating pair formation systems.…”
Section: Discussionsupporting
confidence: 91%
“…Overnight cultures were initiated in LB broth (with 25 μg/mL kanamycin for RP4 plasmid carrying strains) before 1:100 dilution was performed into fresh LB medium and mixed thoroughly. The growth of the bacterial strains was determined with a Bioscreen C MBR machine (Bioscreen, Oy Growth Curves Ab Ltd.) for 24 h as described previously ( 56 ). The growth curves, growth rate (r), and maximum yield (K) were calculated from the data using RStudio (R version 4.2.1), with R source code based on a previously described MATLAB code ( 68 ).…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic resistance is the interplay between genotype and environmental conditions. The inconsistency between MDR phenotypes and antimicrobial resistant (AMR) genes may be related to the resistance genes located at mobilizable or conjugative plasmids that may disappear when there is a change in ecological settings, such as time of storage and subculturing that changes the plasmid’s fitness [ 32 33 ]. Whole genome sequencing (WGS)-based AMR prediction is currently an alternative to conventional molecular PCR and phenotypic AMR characterization studies.…”
Section: Discussionmentioning
confidence: 99%
“…So far, we have implicitly talked about plasmid-plasmid interactions from the perspective of pairs of plasmids. When there are more than two types of plasmids present in a host cell, there will be higher-order interactions between plasmids that will need to be taken into account [156,193].…”
Section: Interactions With Other Plasmids and Mobile Genetic Elementsmentioning
confidence: 99%
“…In addition to interference between gene regulation or the physiological processes of the plasmid and chromosome [14, 25, 133, 134, 136–139], the causes of this fitness cost include bacterial stress responses to foreign DNA [14, 25], the cost of plasmid replication and gene expression [14, 25, 140, 141] and the possibility of disruption of host genes by the plasmid recombining with the chromosome [25]. These costs can be reduced or eliminated by compensatory evolution of the plasmid [137, 142–144], the host chromosome [145–150], or both [138, 151–154], and evolution experiments have shown that this occurs regularly, especially if selection for the plasmid ensures that it is maintained before compensation is complete [138, 142–146, 148, 149, 151–153, 155, 156]; there is also some observational evidence of compensatory evolution in plasmids in the wild [157, 158]. The coevolved plasmid and chromosome produced by compensatory evolution are specifically adapted to each other, and to existence as components of a single genome [26] (although some compensatory changes on the plasmid are general enough to also reduce the fitness cost in other hosts [152]), even to the extent that coevolved cells cured of the plasmid have lower fitness than wild-type cells [145, 159, 160].…”
Section: Ecology Of Plasmidsmentioning
confidence: 99%